2015
DOI: 10.1016/j.jacc.2015.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Defects of High-Density Lipoproteins in Coronary Artery Disease Caused by Low Sphingosine-1-Phosphate Content

Abstract: Reduced HDL-S1P content contributes to HDL dysfunction in CAD. It can be efficiently increased by S1P-loading in vitro and in vivo, providing a novel approach to correcting HDL dysfunction in CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 30 publications
4
116
0
Order By: Relevance
“…A highly significant inverse relationship exists between HDL-containing S1P levels and the occurrence of ischemic heart disease (179 ). S1P levels were also reduced in patients with acute MI and stable CAD, with preclinical rodent assays demonstrating that administering S1P in vivo can correct HDL dysfunction in CAD (180,181 ). These data suggest that S1P has an active involvement in CVD pathogenesis and that future assays quantifying S1P content of HDL could be useful as a cardiovascular risk biomarker.…”
Section: Composition and Role Of Hdl-associated Lipidsmentioning
confidence: 76%
“…A highly significant inverse relationship exists between HDL-containing S1P levels and the occurrence of ischemic heart disease (179 ). S1P levels were also reduced in patients with acute MI and stable CAD, with preclinical rodent assays demonstrating that administering S1P in vivo can correct HDL dysfunction in CAD (180,181 ). These data suggest that S1P has an active involvement in CVD pathogenesis and that future assays quantifying S1P content of HDL could be useful as a cardiovascular risk biomarker.…”
Section: Composition and Role Of Hdl-associated Lipidsmentioning
confidence: 76%
“…89 Moreover, a reduced HDL-associated S1P content has been related to defects in S1P-dependent activation of ERK1/2 and Akt signaling pathways as well as eNOS phosphorylation at Ser1177 in vascular endothelial cells in patients with CAD. 116 In vitro loading of both healthy and CAD HDL particles with additional S1P improved the effects of HDL on endothelial ERK1/2 and Akt activation, eNOSactivating phosphorylation, and vasorelaxation in pre-contracted arteries. 116 This loading may not only be an experimental model but may also happen in vivo, because HDL induces S1P efflux from erythrocytes and other cells by apoM dependent and -independent mechanisms.…”
Section: Sphingolipidsmentioning
confidence: 91%
“…116 In vitro loading of both healthy and CAD HDL particles with additional S1P improved the effects of HDL on endothelial ERK1/2 and Akt activation, eNOSactivating phosphorylation, and vasorelaxation in pre-contracted arteries. 116 This loading may not only be an experimental model but may also happen in vivo, because HDL induces S1P efflux from erythrocytes and other cells by apoM dependent and -independent mechanisms. 103 It may hence well be that HDL are locally uploaded with S1P by endothelial cells or circulating blood cells so that the ex vivo measured S1P levels in HDL underestimate the in vivo situation.…”
Section: Sphingolipidsmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been recently suggested that S1P bound to ApoM-containing HDL activates endothelial S1PR1 and results in a suppression of inflammatory responses (53). Although the structure of the ApoM protein supports the binding of S1P and HDL-associated S1P is bound specifically to ApoM such that ApoM-containing HDL contain S1P, whereas HDL devoid of ApoM do not (52), Sattler et al (54) have clearly demonstrated that S1P can be loaded in vitro or in vivo onto HDL, which are virtually absent of ApoM, and restore the defective signaling of the HDLs. We have shown previously that the S1P content of HDL can be increased significantly after in vitro incubation of the HDL particle with molecular S1P (16) and that this supplemented S1P is biologically active.…”
Section: Discussionmentioning
confidence: 99%